Syntax in language and music: what is the right level of comparison? - Asano, Rie; Boeckx, Cedric (Frontiers in Psychology, 2015)
It is often claimed that music and language share a process of hierarchical structure building, a mental “syntax”. Although several lines of research point to commonalities, and possibly a shared syntactic component, differences between “language syntax” and “music syntax” can also be found at several levels: conveyed meaning, and the atoms of combination, for example. To bring music and language closer to one another, some researchers have suggested a comparison between music and phonology (‘phonological syntax’), but here too, one quickly arrives at a situation of intriguing similarities and obvious differences. In this paper we suggest that a fruitful comparison between the two domains could benefit from taking the grammar of action into account. In particular, we suggest that what is called “syntax” can be investigated in terms of goal of action, action planning, motor control, and sensory-motor integration. At this level of comparison, we suggest that some of the differences between language and music could be explained in terms of different goals reflected in the hierarchical structures of action planning: the hierarchical structures of music arise to achieve goals with a strong relation to the affective-gestural system encoding tension-relaxation patterns as well as socio-intentional system, whereas hierarchical structures in language are embedded in a conceptual system that gives rise to compositional meaning. Similarities between music and language are most clear in the way several hierarchical plans for executing action are processed in time and sequentially integrated to achieve various goals.